Asociaciones entre trauma, culpa, autocrítica y síntomas de trastornos emocionales en mujeres sobrevivientes de violencia de género en colombia (2021)
Women are more often victims of gender-based violence (GBV), especially in intimate partner relationships (WHO, 2017). One third (30%) of women in intimate partner relationships have reported at some point in their lives being victims of violence, physical and/or sexual, by their intimate partner (WHO, 2017). The aim of the research was to analyze the relationships between permissive beliefs of GBV, forms of violence and emotional problems, as well as the relationships between severity of trauma, guilt, self-criticism and symptoms of emotional problems. Descriptive correlational study with 50 women victims of intimate partner violence. Results: confirmation of the positive relationship between guilt and self-criticism, with all symptoms of emotional problems assessed (PTSD, anxiety and depression); a positive relationship of trauma symptoms with guilt and self-criticism was found; and sexual violence was the only form of violence that showed a positive relationship with trauma and guilt. Permissive beliefs of gender-based violence were negatively related to emotional and sexual violence.